2022
DOI: 10.1038/s41419-022-04998-0
|View full text |Cite
|
Sign up to set email alerts
|

β2-adrenergic receptor promotes liver regeneration partially through crosstalk with c-met

Abstract: The β2-adrenergic receptor (β2AR) is a G protein-coupled receptor (GPCR) that mediates the majority of cellular responses to external stimuli. Aberrant expression of β2AR results in various pathophysiological disorders, including tumorigenesis, but little is known about its role in liver regeneration. This study aims to investigate the impact and the underlying mechanism of β2AR in liver regeneration. Here, we found that β2AR was upregulated during liver regeneration induced by 70% PH. Deletion of β2AR in mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Studies have demonstrated that several adrenergic receptors are involved in the pathogenesis of liver disease. ISO, a non-selective beta-adrenergic receptor agonist, has been revealed to induce the proliferation of progenitor stem liver cells and alleviate the progression of APAP-induced liver failure [12]. Furthermore, beta-adrenergic receptors have been shown to accelerate the proliferation of hepatocytes to mitigate the development of liver failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that several adrenergic receptors are involved in the pathogenesis of liver disease. ISO, a non-selective beta-adrenergic receptor agonist, has been revealed to induce the proliferation of progenitor stem liver cells and alleviate the progression of APAP-induced liver failure [12]. Furthermore, beta-adrenergic receptors have been shown to accelerate the proliferation of hepatocytes to mitigate the development of liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, prazosin, an antagonist of α-adrenergic receptors, alleviates liver injury, while propranolol, an antagonist of β-adrenergic receptors, exacerbates it [10]. In particular, substances that stimulate the adrenergic system and receptors have the potential to enhance the growth of precursor cells and liver cells, as well as provide defense against sudden liver damage [10][11][12]. The expansion of precursor cells only constitutes a minor fraction of liver cells, whereas other majority of non-parenchymal hepatic cells, such as Kupffer cells, also play a signi cant role in regulating the advancement of in ammation.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of beta-adrenergic receptors by neurotransmitters has been known to contribute to the regulation of SNS on normal and pathogenesis of liver disease diseased liver function. As a non-selective beta-adrenergic receptor agonist, ISO has been revealed to induce the proliferation of progenitor stem liver cells and alleviate the progression of acetaminophen-induced liver injury [ 12 ]. Furthermore, beta-adrenergic receptors were able to accelerate the proliferation of parenchymal hepatocytes to mitigate the development of liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, prazosin effectively reduces liver injury by blocking alpha-adrenergic receptors, while propranolol, a beta-adrenergic receptor antagonist, can exacerbate it [ 10 ]. Specifically, substances that stimulate the adrenergic system and its receptors have the potential to encourage growth of precursor cells and hepatocytes and also provide defense against sudden liver damage [ 10 12 ]. However, the proliferation of progenitor cells accounts for only a small proportion of liver cells, while the vast majority of non-parenchymal hepatic cells, including Kupffer cells, are also important in modulating the progression of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, α and β receptor expressions were described in hepatocytes. [50][51][52] In primary cultures, hepatic stellate cells (HSCs) express α1a, α1b, α1d, α2b, β1, β2, β3, and NPY receptors. [53][54][55] The liver resident macrophage Kupffer cells were reported to express all the nine adrenergic reports.…”
Section: Hepatic Nerves and The Intrahepatic Nerve-mediated Cellular ...mentioning
confidence: 99%